Do targeted user fee exemptions reach the ultra-poor and increase their healthcare utilisation?: a panel study from Burkina Faso - Beaugé, Yvonne; De Allegri, Manuela; Ouédraogo, Samiratou; Bonnet, Emmanuel; Kuunibe, Naasegnibe; Ridde, Valéry (International journal of environmental research and public health, 2020)
Background: A component of the performance-based financing intervention implemented in Burkina Faso was to provide free access to healthcare via the distribution of user fee exemption cards to previously identified ultra-poor. This study examines the factors that led to the receipt of user fee exemption cards, and the effect of card possession on the utilisation of healthcare services. Methods: A panel data set of 1652 randomly selected ultra-poor individuals was used. Logistic regression was applied on the end line data to identify factors associated with the receipt of user fee exemption cards. Random-effects modelling was applied to the panel data to determine the effect of the card possession on healthcare service utilisation among those who reported an illness six months before the surveys. Results: Out of the ultra-poor surveyed in 2017, 75.51% received exemption cards. Basic literacy (p = 0.03), living within 5 km from a healthcare centre (p = 0.02) and being resident in Diébougou or Gourcy (p = 0.00) were positively associated with card possession. Card possession did not increase health service utilisation (β = −0.07; 95% CI = −0.45; 0.32; p = 0.73). Conclusion: A better intervention design and implementation is required. Complementing demand-side strategies could guide the ultra-poor in overcoming all barriers to healthcare access.
Gesehen am 02.12.2020